Continuity effects in the perception of sounds - Reinier PLOMP (Archives of Acoustics)
The paper presents the phenomenon of continuity in the preception of sounds in condition of uncomplete information. On the basis of examples of perception of sounds with gliding frequency changes interrupted by noise burst, modulated tones "damaged" in similar way, it is concluded that under specific conditions the hearing system is able to restore the original sound patterns. Other examples of continuity are also given, especially, of alternating tone sequences which demonstrate that perception is not a passive process but a highly active one.